Association between dyslipidemia and depression: a cross-sectional analysis of NHANES data from 2007 to 2018 - Xuemin Zhong; Jinxuan Ming; Changqing Li (BMC Psychiatry)
Abstract Background The relationship between depression and dyslipidemia remains controversial, with inconsistent findings across studies. This study aimed to investigate the association between blood lipid levels and depression using data from the National Health and Nutrition Examination Survey (NHANES) spanning from 2007 to 2018. Methods This cross-sectional study included 12,819 adult participants from NHANES. Depression was assessed using a nine-item depression screening instrument. Serum lipid levels, including total cholesterol (TC), high-density lipoprotein cholesterol (HDL-C), low-density lipoprotein cholesterol (LDL-C), and triglycerides (TG), were measured using Roche modular P and Roche Cobas 6000 chemistry analyzers. Survey-weighted multiple logistic regression was used to assess the relationships between serum lipid levels and depression. Results We observed a statistically significant negative association between HDL levels and depression (odds ratio [OR]: 0.72, 95% confidence interval [CI]: 0.58–0.90). After adjustments for covariates, HDL-C, TG, and the triglyceride glucose (TyG) index showed significant associations with depression (ORs: 0.66, 1.08, and 1.01, respectively). A linear correlation was observed between HDL-C levels and depression (P < 0.01), while TG levels and the TyG index exhibited nonlinear associations (p < 0.01 and p < 0.05, respectively). No significant positive associations were observed between increased TC or LDL-C levels and the risk of depression. Conclusions High HDL-C levels were negatively associated with depression, while TG levels and the TyG index were positively associated with depression. Clinical attention should be given to the detection of lipid levels in patients with depression.